GIS Habitat Based Models Spatial Analysis to Determine The Suitability Of Habitat For Elephants - Agus Sukoco (International Conference on Engineering and Technology Development (ICETD), 2012)
Model of geographic about of Sumatran elephant habitat, based on the potential food, water, the pools to determine the suitability of habitat for Sumatran elephants, with the scoring process of spatial analysis and overlay.Overlay and analysis of the suitability of our food, our water and puddles and topografi a limiting factor.The importance of the areas of potentially suitable habitat for Sumatran elephants.